Dynamics of Synthetic Membraneless Organelles in Microfluidic Droplets. (3rd September 2019) - Linsenmeier, Miriam; Kopp, Marie R. G.; Grigolato, Fulvio; Emmanoulidis, Leonidas; Liu, Dany; Zürcher, Dominik; Hondele, Maria; Weis, Karsten; Capasso Palmiero, Umberto; Arosio, Paolo
Abstract: Cells can form membraneless organelles by liquid–liquid phase separation. As these organelles are highly dynamic, it is crucial to understand the kinetics of these phase transitions. Here, we use droplet‐based microfluidics to mix reagents by chaotic advection and observe nucleation, growth, and coarsening in volumes comparable to cells (pL) and on timescales of seconds. We apply this platform to analyze the dynamics of synthetic organelles formed by the DEAD‐box ATPase Dhh1 and RNA, which are associated with the formation of processing bodies in yeast. We show that the timescale of phase separation decreases linearly as the volume of the compartment increases. Moreover, the synthetic organelles coarsen into one single droplet via gravity‐induced coalescence, which can be arrested by introducing a hydrogel matrix that mimics the cytoskeleton. This approach is an attractive platform to investigate the dynamics of compartmentalization in artificial cells. Abstract : Nicht nur ein Tröpfchen auf den heißen Stein : Ein Tröpfchen‐Mikrofluidik‐Assay zur Untersuchung der Nukleations‐, Wachstums‐ und Vergröberungskinetik bei der Bildung synthetischer membranloser Organellen mittels Flüssig/Flüssig‐Phasentrennung (LLPS) in zellartigen Kompartimenten wurde entwickelt. Der Assay erlaubt die Aufklärung der Mechanismen, die die Dynamik der Kompartimentbildung räumlich und zeitlich bestimmen.